2021
DOI: 10.1111/peps.12479
|View full text |Cite
|
Sign up to set email alerts
|

Asking how to fish vs. asking for fish: Antecedents and outcomes of different types of help‐seeking at work

Abstract: In the modern workplace, it is virtually impossible to succeed without seeking any help from others. Despite its widely recognized importance, several areas surrounding help‐seeking have not yet been clearly understood in the organization literature. Specifically, it is unclear whether seeking help always benefits employees in need, and how various work demands drive help‐seeking behavior in different ways. In this research, we drew from the dual‐type view of help‐seeking (i.e., autonomous and dependent help‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 126 publications
(181 reference statements)
1
26
0
Order By: Relevance
“…At the intersection of helping recipients and helping actors lies the reason for why help occurred in the first place—was help solicited or not. Research shows employees may ask for specific types of help from their coworkers (Geller & Bamberger, 2012), and a recent article showed that this request may be driven by the amount of challenge or hindrance stressors employees experience (Liu et al, 2021). Yet, help can, of course, also be provided without a request (Bolino & Grant, 2016; Spitzmuller & Van Dyne, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…At the intersection of helping recipients and helping actors lies the reason for why help occurred in the first place—was help solicited or not. Research shows employees may ask for specific types of help from their coworkers (Geller & Bamberger, 2012), and a recent article showed that this request may be driven by the amount of challenge or hindrance stressors employees experience (Liu et al, 2021). Yet, help can, of course, also be provided without a request (Bolino & Grant, 2016; Spitzmuller & Van Dyne, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Based on resource allocation theory, Fu et al (2021) found that help-giving is negatively related to objective individual job performance. Lim et al (2020) and Liu et al (2021) pointed out that help-seeking in relation to problems can also bring about a lack of confidence in the ability of the team member and affect performance. Our study introduced and tested the idea of interaction between team help-seeking and -giving, rather than their separate discussion and consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Help-seeking refers to the solicitation of others' emotional or instrumental assistance to manage either work-related or personal problems that have a bearing on performance (Lim et al, 2020), which occurs mainly in problem situations. The antecedent variables of help-seeking are perceived challenge pressure (Zhao et al, 2021), learning climate (De Vos et al, 2021), stressors (Liu et al, 2021), task interdependence, and so on. In new venture teams, team help-seeking is aimed at jointly solving entrepreneurial problems and dealing with the uncertainty of the start-up process.…”
Section: Team Helpmentioning
confidence: 99%
“…Service workers may seek, receive and return help to coworkers, which reflects the fundamental ideal of social exchange (e.g. Hofmann et al , 2009; Liu et al , 2021). When mistreated by customers, employees are likely to feel that such customers provided negative feedback, which contradicts their task goal.…”
Section: Introductionmentioning
confidence: 99%